DYNAMICS OF ORGANIZING AREMANIA COHESIVENESS - Widijatmoko, E.K.; Soesilowati, Etty; Rachman, Maman; Handoyo, Eko (International Journal of Psychosocial Rehabilitation, 2020)
The support team’s cohesiveness has an important role to play in a soccer match, which is to be fun. However, the support team became frightening, worrying because the actions of some supporters ignored cohesiveness. The supporting cohesion role is an inherent part of the entertainment side of a soccer match. The purpose of this study is to describe the dynamics of organizing Aremania cohesiveness. The research questions are as follows: 1) what aspects of Aremania cohesiveness are regulated, 2) the extent to which Aremania cohesiveness has been regulated, 3)how to strengthen Aremania cohesiveness is regulated. The qualitative approach chosen in this study, the type of research model, the study of phenomenology. Data collection was carried out using participant observation and in-depth structured interviews. Data validity test uses data triangulation which is divided into three namely technique, time and source. Field data were analyzed using the interactive model of Miles and Huberman. The research location is Bandungrejosari Subdistrict, Sukun Regency, Malang City. The results of the study, the cohesiveness of Aremania governed aspects of personality, interpersonal aspects and aspects of group performance. Aremania consistently transmits social cohesiveness, within groups, communities and regions. Cohesiveness through personality composition, interpersonal cohesiveness and the performance of the Aremania group. Aremana’s individual diversity forms a personality composition within the team’s cohesiveness and group performance. This encourages the emergence of community cohesion and group cohesiveness to work towards cohesiveness performance.